2021
DOI: 10.3389/fpsyt.2021.623499
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms, Quality of Life, and Stress Burden in Caregivers of Patients With Severe Mental Illness: An Underestimated Health Concern

Abstract: Caregivers of patients with severe mental disorders experience a heavy stress burden that can manifest as psychiatric symptoms mimicking posttraumatic stress disorder (PTSD) and can negatively impact interpersonal relationships and work performance. The present study investigated the prevalence of PTSD symptoms, quality of life (QoL), and stress burden in caregivers of patients with severe mental illness. A total of 70 caregivers of severely mentally ill patients and 70 control subjects who were caregivers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
(27 reference statements)
3
10
0
Order By: Relevance
“…Furthermore, the prevalence of probable PTSD in this study (12.1%) exceeded the general lifetime prevalence of PTSD (worldwide between 1.3 and 8.8%; ( 31 )) and in the Netherlands (7.4%; ( 30 )). These findings are in line with previous research which showed that a severe or chronic illness of a relative can be experienced as a traumatic stressor and has been associated with manifestations of PTSD symptomatology ( 32 34 ). In addition, as hypothesized, family members who reported PWS-related trauma scored higher on PTSD symptoms than participants who experienced a different, non PWS-related traumatic event.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the prevalence of probable PTSD in this study (12.1%) exceeded the general lifetime prevalence of PTSD (worldwide between 1.3 and 8.8%; ( 31 )) and in the Netherlands (7.4%; ( 30 )). These findings are in line with previous research which showed that a severe or chronic illness of a relative can be experienced as a traumatic stressor and has been associated with manifestations of PTSD symptomatology ( 32 34 ). In addition, as hypothesized, family members who reported PWS-related trauma scored higher on PTSD symptoms than participants who experienced a different, non PWS-related traumatic event.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 5034 caregivers from 23 countries were included in the analysis. Six studies were conducted in Nigeria [ 18 , 40 , 41 , 42 , 43 , 44 ], five studies in Brazil [ 45 , 46 , 47 , 48 , 49 ], three studies each in Nepal [ 50 , 51 , 52 ] and Turkey [ 53 , 54 , 55 ], two studies each in Hong Kong [ 56 , 57 ], the USA [ 58 , 59 ], and Taiwan [ 60 , 61 ], and one study each in Africa [ 62 ], China [ 63 ], Chile [ 64 ], Egypt [ 65 ], Greece [ 66 ], India [ 67 ], Ireland [ 68 ], Italy [ 69 ], Japan [ 70 ], Jordan [ 71 ], Kuwait [ 72 ], Poland [ 73 ], Portugal [ 74 ], Singapore [ 75 ], Spain [ 76 ], and the Netherlands [ 77 ]. In terms of study setting, 11 studies were conducted in the community, 18 studies in the hospital, and nine studies in the clinic (refer to Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“… Pooled prevalence of caregiver burden among caregivers of patients with mental illness [ 18 , 40 , 41 , 44 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 58 , 59 , 60 , 62 , 63 , 64 , 65 , 68 , 69 , 70 , 71 , 72 , 75 , 77 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations